2016
DOI: 10.5586/am.1067
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies of fungi in the Biebrza National Park (NE Poland). Part III. Micromycetes – new data

Abstract: Ecological information concerning 292 fungal taxa is reported as a result of two surverys in the Biebrza National Park. Most data presented come from the 5-day all-fungi inventory of the Polish Mycological Society in 2013, and 47 species were recorded during studies in the Biele Suchowolskie fen in 2008/2009. In total, 27 species of zygomycetes, 232 ascomycetes (including anamorphs) and 27 basidiomycetes (mainly Pucciniales). Additionaly some representatives of fungi-like organisms from Stramenopiles (4 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Until 2000, detailed mycological observations have been conducted only in a few of them (e.g., [2][3][4]). The majority of the objects under this form of protection have been studied in recent years (e.g., [5][6][7][8][9][10][11][12]). However, the state of recognition of diversity fungi in many Polish national parks is still not enough.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2000, detailed mycological observations have been conducted only in a few of them (e.g., [2][3][4]). The majority of the objects under this form of protection have been studied in recent years (e.g., [5][6][7][8][9][10][11][12]). However, the state of recognition of diversity fungi in many Polish national parks is still not enough.…”
Section: Introductionmentioning
confidence: 99%
“…It also pertains to the Biebrza National Park, which before the year 2012 had not been under mycological surveillance. During short-term study conducted in this area in the years 2012-2013, analyses revealed as many as 480 species of microscopic fungi [20,21]. These investigations, however, did not include species of protected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Thesium ebracteatum occurs in national parks: Białowieża National Park, Kampinos National Park, Biebrza National Park, and Wigry National Park [17,18]. Among these, parasite microfungi were thoroughly elaborated in the Białowieża National Park [19] and partly in the Biebrza National Park [20,21]. Digital signature This PDF has been certified using digital signature with a trusted timestamp to assure its origin and integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Main sources 1 Szczecin City and surroundings [119,160,186] Słowiński National Park [129,130,142,161] 2 Poznań City [166] Noteć River valley [115] Bydgoszcz City [116] 3 Białowieża National Park [123] Biebrza National Park Own data [140,141] 4 Łuk Mużakowa Landscape Park Own data…”
Section: Area No* Localities Surveyedmentioning
confidence: 99%
“…Most of the data on the occurrence of Asteromella species in Poland were listed in the literature-based checklist of Polish micromycetes in 2008 [139]. The most recent records hail from studies conducted in the Biebrza and Słowiński national parks [140][141][142]. …”
mentioning
confidence: 99%